Study on the Mechanisms of Multiple Myeloma Cells Promoting M2 Macrophage Polarization through PI3K/AKT Signaling Pathway - PENG Yilun, LI Yang, WANG Xiaotao (Zhongguo quanke yixue, 2024)
Background The incidence of multiple myeloma has long been high, however, there are fewer studies on phosphatidylinositol 3-kinase (PI3K) /serine-threonine kinase (AKT) signaling pathway and M2 macrophage polarization promoting the progression of multiple myeloma. Objective To investigate the expression of M2 macrophages in patients with multiple myeloma and the mechanism of PI3K/AKT signaling pathway promoting M2 macrophage polarization. Methods Forty-eight multiple myeloma patients diagnosed in the Department of Hematology of the Affiliated Hospital of Guilin Medical University from October 2021 to April 2022 were selected as the test group, and thirty healthy volunteers (healthy donors of blood marrow transplantation) in the same period were selected as the control group. Peripheral blood was taken from the 2 group and mononuclear cells were isolated, the proportion of M2 macrophages was determined by flow cytometry. RPMI8226 cells were subcultured by cell passage, and mononuclear macrophages THP-1 cells were cultured as macrophages by phorbol ester differentiation. According to the experimental requirements, tumor cells were cultured and transfected with siRNA to silence phosphatase and tensin homolog (PTEN) and divided into three groups, including blank group, siRNA-PTEN experimental group, and siRNA control group; the supernatants of the above three groups were collected and added to the macrophage co-culture system and then divided into four groups including M0 macrophage group, tumor cell supernatant group, siRNA-PTEN supernatant group, and siRNA supernatant group. The protein expression levels of AKT, p-AKT, PI3K-p85, and p-PI3K-p85 in the blank group, siRNA-PTEN experimental group, and siRNA control group of multiple myeloma cell culture were determined by Western blot assay. The mRNA expression levels of MMP2 and MMP9 in the blank group, siRNA-PTEN experimental group and siRNA control group were determined by fluorescence quantitative polymerase chain reaction (PCR) . The expression levels of specific antibodies CD163, CD206, and F4/80 in M2 macrophages in M0 macrophage group, tumor cell supernatant group, siRNA-PTEN supernatant group, and siRNA supernatant group were determined by flow cytometry. The mRNA expression levels of arginase 1 (ARG-1) and interleukin 10 (IL-10) in M0 macrophage group, tumor cell supernatant group, siRNA-PTEN supernatant group, and siRNA supernatant group were determined by fluorescence quantitative PCR. Results The expression level of M2 macrophages was higher in the test group than that in the control group (t=0.855, P<0.001) . The protein expression levels of p-AKT/AKT and p-PI3K-p85/PI3K-p85 in the siRNA-PTEN experimental group were higher than the blank group and siRNA control group (P<0.05) . The mRNA expression levels of MMP2 and MMP9 in the siRNA-PTEN experimental group were higher than the blank group and siRNA control group (P<0.05) . M2 macrophage specific antibody CD163+F4/80 and CD206+F4/80 in the siRNA-PTEN supernatant group were higher than the tumor cell supernatant and siRNA-PTEN supernatant group (P<0.05) . The mRNA expression levels of ARG-1 and IL-10 in the siRNA-PTEN supernatant group were higher than the tumor cell supernatant group and siRNA supernatant group (P<0.05) . Conclusion M2 macrophages are upregulated in multiple myeloma patients, and multiple myeloma cells can promote M2 macrophage polarization through activation of the PI3K/AKT signaling pathway, thereby regulating the myeloma cell microenvironment.